Improving Prevention Compliance through Appropriate Incentives: Theoretical Modelling and Empirical Evidence - Udo Schneider; Jürgen Zerth (Swiss Journal of Economics and Statistics, 2011)
This paper explores the effects of insurance parameters and complementary information environment on the patient's primary prevention activity. The theoretical model is based on a principal-agent setting in which the patient acts as an agent in deciding about his prevention efforts. The insurer chooses the coverage level and therefore the level of patient's cost sharing and decides on his monitoring activities. The empirical analysis looks at the patient's prevention decision in the case of smoking. Using a hazard model in discrete time, the decision to change behaviour depends on health status, education, age and working time but not on the insurance system.
Keywords: I12; D82; C23; 330; incentives in prevention; information distribution; hazard model